2022
DOI: 10.3346/jkms.2022.37.e25
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Treatment of Vulvar Cancer From 2014−2018: A Nationwide Population-Based Study in Korea

Abstract: Background Vulvar cancer is one of the rare gynecologic malignancies. Despite the recent increasing trend of vulvar cancer in western countries due to the increased infection of human papillomavirus, there has been no study for population-based incidence of vulvar cancer in Korea. We aimed to investigate the prevalence and treatment of vulvar cancer in South Korea between 2014 and 2018. Methods Data from patients diagnosed and treated with vulvar cancer between 2014 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Age specific prevalence analysis, according to decade of life, revealed maximum cases (12 out of 47) in eighth decade of life i.e. between 70 to 79 years of age and minimum cases (4/47) in 4 th decade (between 30 to 39 years) of life; which consolidated the outcome of previous study by Ouh et al [20]. No cases in our analysis was below 30 years of age.…”
Section: Discussionsupporting
confidence: 89%
“…Age specific prevalence analysis, according to decade of life, revealed maximum cases (12 out of 47) in eighth decade of life i.e. between 70 to 79 years of age and minimum cases (4/47) in 4 th decade (between 30 to 39 years) of life; which consolidated the outcome of previous study by Ouh et al [20]. No cases in our analysis was below 30 years of age.…”
Section: Discussionsupporting
confidence: 89%
“…From 2001 to 2017, the incidence rate of vulvar cancer related to human papilloma virus (HPV) in the United States increased by 1.2% every year, especially among women aged 50-69, while the overall incidence rate of non-HPVrelated cancer remained stable [5]. Comparatively, a South Korean population-based study from 2014 to 2018 showed no significant change in the incidence of vulvar cancer during a similar time period [6]. According to the estimation of the American Cancer Association, there will be an estimated 6330 new vulvar cancer cases and 1560 related death in 2022 [1].…”
Section: Introductionmentioning
confidence: 99%